From Cost Efficiency to Economic Efficiency: The Mediating Role of Economic Efficiency on the Privatization of Government Airports and its Contribution to Economic Growth - AlAbdulkader, Muath; Hazlina Binti Abd Kadir (International Journal of Computational and Experimental Science and Engineering, 2025)
The privatization of public airport facilities constitutes a strategic initiative aimed at enhancing airline operational efficiency and reducing financial expenditures, thereby fostering economic growth. While cost efficiency remains the primary objective in most privatization efforts, its long-term economic implications remain limited unless economic efficiency is systematically incorporated. This study explores the role of economic efficiency as a mediating factor that links cost efficiency and the success of airport privatization with broader economic growth benefits. Employing Public Choice Theory, Transaction Cost Economics, and Principal-Agent Theory as theoretical underpinnings, this research analyzes the impact of privatization on economic value creation and short-term financial performance through cost-reduction strategies such as outsourcing and Total Quality Management. Using a mixed-methods approach, this study assesses the extent to which economic efficiency influences investment levels, employment generation, and infrastructure development in privatized airports. The findings suggest that while cost efficiency enhances operational effectiveness, economic efficiency plays a crucial role in ensuring sustained economic progress. Privatization, therefore, facilitates broader economic gains by leveraging economic efficiency strategies, aligning short-term cost savings with long-term economic advancements that benefit both airport operators and industry stakeholders.